THE EFFECT OF PROFITABILITY MODERATION ON CORPORATE SOCIAL RESPONSIBILITY AND FIRM VALUE: EVIDENCE FROM INDONESIA - Titisari, Kartika Hendra; Utama, I Made Karya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Previous studies have shown that the relationship between corporate social responsibily (CSR) and firm value (FV) is still inconsistent. Therefore, the objective of this research is to test the impact of corporate social responsibility towards firm value and the profitability as moderation variable. Profitability is used since it is certainly inseparable from funding sources derived from the company's activity. Sample of this research is companies listed in Indonesia Stock Exchange (IDX) that publish sustainability report of 2010 – 2016 periods with 27 companies and 170 observations. Linear regression is used in analyzing hypotheses. The result of the test shows that CSReconomy takes effect on the firm value while CSRsocial and CSRenvironment have no effect towards firm value. The further test shows that profitability is proven to moderating the relationship of CSReconomy and CSRsocial towards firm value. In Indonesia, the company’s sustainability report is voluntarily disclosed. Thus, this research recommends Sustainability Report to be mandatory discloded in Indonesia Stock Exchange (IDX).